2022
DOI: 10.3390/ph15091149
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Potential of Flavonoids against Neurotropic Viruses

Abstract: Flavonoids are a group of natural compounds that have been described in the literature as having anti-inflammatory, antioxidant, and neuroprotective compounds. Although they are considered versatile molecules, little has been discussed about their antiviral activities for neurotropic viruses. Hence, the present study aimed to investigate the pharmacological potential of flavonoids in the face of viruses that can affect the central nervous system (CNS). We carried out research from 2011 to 2021 using the Pubmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 116 publications
0
4
0
Order By: Relevance
“…One of these was MYR, having a docking score of −21.987 kcal/mol and, consequently, was considered as an inhibitor of NS2B-NS3. 119 The pharmacological potential of flavonoids against neurotropic viruses has been recently reviewed by Castro e Silva et al 120…”
Section: Antiviral Significancementioning
confidence: 99%
See 1 more Smart Citation
“…One of these was MYR, having a docking score of −21.987 kcal/mol and, consequently, was considered as an inhibitor of NS2B-NS3. 119 The pharmacological potential of flavonoids against neurotropic viruses has been recently reviewed by Castro e Silva et al 120…”
Section: Antiviral Significancementioning
confidence: 99%
“…One of these was MYR, having a docking score of −21.987 kcal/mol and, consequently, was considered as an inhibitor of NS2B-NS3. 119 The pharmacological potential of flavonoids against neurotropic viruses has been recently reviewed by Castro e Silva et al 120 Antiviral effects of 60% aqueous methanol extracts of Zanthoxylum armatum and Hibiscus sabdariffa were demonstrated on murine norovirus. 121 Of the constituents, the phenolic compounds myricetin, quercetin, kaempferol, and luteolin exhibited significant activity, but quercetin showed the most significant logarithmic viral reductions.…”
Section: Antiviral Significancementioning
confidence: 99%
“…In this context, the importance of natural products (NPs) as sources of new drugs is highlighted due to their privileged structures and high safety profile . Within NPs, flavonoids represent one of the largest and most diverse groups, showing promising biological activities such as anticancer, antimicrobial, , antiparasitic, and anti-inflammatory. Furthermore, flavonoids have also been described as a class of phytochemicals with potential antiviral activity against different DNA and RNA viruses, such as HIV, HSV, influenza, SARS, SARS-CoV-2, and others. , …”
mentioning
confidence: 99%
“…20−22 Furthermore, flavonoids have also been described as a class of phytochemicals with potential antiviral activity against different DNA and RNA viruses, such as HIV, HSV, influenza, SARS, SARS-CoV-2, and others. 23,24 Concerning the SARS-CoV-2 outbreak, in 2020 Su et al 25 reported the natural flavone baicalein (Figure 1) as the first noncovalent and non-peptidomimetic inhibitor of SARS-CoV-2 main protease (M pro ), also known as 3CL pro (IC 50 = 0.9 μM), by determination of the crystal structure of the enzyme−ligand complex. The antiviral activity was reported in a cell-based system, using Vero E6 (African green monkey kidney cells) as the model (EC 50 = 2.9 μM).…”
mentioning
confidence: 99%